Assessing government to business services performance: the role of human and organizational factors - Hussin, Husnayati; Kassim, Erne Suzila (2010)
In an attempt to deliver better service performance to businesses and improve the interactions, many public organizations have transformed their business activities by adopting information systems. The reformations of the government-to-business have led to the evaluation of the system service performance and investigation of the factors that shape the success of the IS implementation. Hence, the purpose of the study is to assess the government-to-business service performance and explore the human and organizational factors that influence the success. The findings indicate top management support, facilitating condition, user skills and attitude play a major role in influencing the government-to-business system usage among government agencies. In addition, use of IS in the interaction between government and business has significant influence on the service performance, measured as transparency, service quality and information quality. The findings provide a new perspective for public agencies in their future e-government implementation.